Prevalence of chronic pain among cancer survivors in the United States, 2010‐2017. Issue 23 (22nd August 2019) - Sanford, Nina N.; Sher, David J.; Butler, Santino S.; Xu, Xiaohan; Ahn, Chul; Aizer, Ayal A.; Mahal, Brandon A.
Abstract : Background: There are a growing number of cancer survivors in the United States who are at risk for chronic pain due to cancer disease and treatments. The prevalence of chronic pain among cancer survivors has not been comprehensively reported. Methods: This study used data from the National Health Interview Survey (2010‐2017) to compare the prevalence of chronic pain between participants with a cancer diagnosis and participants without one. Adjusted odds ratios (AORs) of having chronic pain were assessed by multivariable logistic regression, which included an age (less than the median age vs greater than or equal to the median age) × cancer diagnosis (yes vs no) interaction term. Among cancer survivors, multivariable logistic regression defined the odds of feeling depressed, feeling worried/nervous/anxious, being unable to work, and needing assistance for activities of daily living (ADLs) and instrumental activities of daily living (IADLs). Results: Among 115, 091 participants, a cancer diagnosis was associated with an increased AOR of chronic pain in comparison with the general population (30.8% vs 15.7%; AOR, 1.48; 95% confidence interval, 1.38‐1.59). Older age was associated with higher odds of chronic pain ( P  < .001 across all increasing age categories); however, the positive association between older age and chronic pain was seen only in participants without cancer and was not seen in those with a cancer diagnosis ( P age×cancer  < .001). Among patients reporting a cancer diagnosis, chronic pain was associated with greater odds of feeling depressed, feeling worried/nervous/anxious, being unable to work, and needing assistance with ADLs or IADLs ( P  < .001 for all). Conclusions: Cancer survivors appear to have a high prevalence of chronic pain, which is associated with worse mental, functional, and employment outcomes. Screening and management of chronic pain should be addressed by policymakers to improve cancer survivorship care. Abstract : In this nationally representative study, approximately one‐third of cancer survivors report having chronic pain; this is nearly double the prevalence in the general population. Among cancer survivors, the presence of chronic pain is associated with worse mental, functional, and employment outcomes.